As representações da mulher construídas a partir da publicidade #CervejeiraSouEu da Ambev - Couto, Kely Cristina Mendonça (2022)
Female objectification happens in the most different contexts and involves several sociocultural factors. Brands from several segments present gender stereotypes and exhibit discourses containing female objectification. Beer brands are great symbols of this type of behavior, which has not pleased many social groups and generates questions. This paper aims to analyze the representations built about women in Ambev's advertising, also observing the readings produced by the public on social networks. For this, i elected the "Cervejeira Sou Eu" campaign, launched by Ambev in March 2021 for the International Women's Day. Were analyzed Comments published by users on the campaign material in question, availables in the main campaign video posted on the brand's official Instagram profile. To analyze the comments Richard Johnson's protocol in the light of cultural studies was used. The content and positioning of the brand stimulated the expression of opinions of the public mapped on the Internet, however, despite the amount of interactions generated, there was not a concise debate on social and gender agendas, showing that it is urgent the formation of thinking critical.